Determinants of the real convergence process in the European Union- a panel analysis 2004-2015 - Młynarzewska-Borowiec, Izabela (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2018)
Convergence in GDP per capita is, undoubtedly, more likely to occur in integration groups and therefore in the group of countries whose economies operate in a similar manner, converging to the same steady state point and creating so-called “convergence clubs”. The “traditional” determinants of economic growth (physical and human capital accumulation, changes in Total Factor Productivity) and the “deep” determinants (level of the openness of economies, quality and efficiency of institutions, capital mobility and diffusion of technology) can be regarded as the key causes of that process. The paper presents a review of the theoretical and empirical studies concerning the influence of the above mentioned determinants on economic growth and convergence. In the empirical part of the paper the real convergence process in the group of the 28 member states of the European Union in the period 2004-2015 is investigated and discussed. Next, panel growth regression model is performed in order to show the influence of the particular determinants on the pace of economic growth and real convergence process in the European Union
Argumenta Oeconomica, 2018, Nr 1 (40), s. 345-363
Keywords: convergence; economic growth; “traditional” and “deep” determinants of economic growth; panel growth regression model